^{2}+ 2x - 4.......................where x = 5

^{2}+ 2(5) - 4

Can someone review the process for this? Thank you!

Tutors, sign in to answer this question.

-x^{2} + 2x - 4.......................where x = 5

substitute x into the equation.

-(5)^{2} + 2(5) - 4

= -25 + 10 - 4

= -19

Shelly J. | Excellent Maths Tutoring for academic successExcellent Maths Tutoring for academic su...

Hi Abby,

For x=5,

-x²+2x-4 = -(5)²+2(5)-4

=-25+10-4

=-15-4

=-19

The evaluation of this expression is in the proper reading of the notation:

–x^2 + 2x – 4

is the same as:

= –(x)^2 + 2(x) – 4

the parentheses are implicit, but inform the evaluator. This is then rewritten more clearly as:

= –(x * x) + 2(x) – 4

which then evaluates under x = 5 by:

= –(5 * 5) + 2 * 5 – 4

where " * " is multiplication. The rest is computation is straightforward, with proper use of order of operations.

Already have an account? Log in

By signing up, I agree to Wyzant’s terms of use and privacy policy.

Or

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Your Facebook email address is associated with a Wyzant tutor account. Please use a different email address to create a new student account.

Good news! It looks like you already have an account registered with the email address **you provided**.

It looks like this is your first time here. Welcome!

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Please try again, our system had a problem processing your request.